2020
DOI: 10.3389/fpls.2020.595439
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Rice GDP-L-Galactose Phosphorylase Constitutive Overexpression on Ascorbate Concentration, Stress Tolerance, and Iron Bioavailability in Rice

Abstract: Ascorbate (vitamin C) is an essential multifunctional molecule for both plants and mammals. In plants, ascorbate is the most abundant water-soluble antioxidant that supports stress tolerance. In humans, ascorbate is an essential micronutrient and promotes iron (Fe) absorption in the gut. Engineering crops with increased ascorbate levels have the potential to improve both crop stress tolerance and human health. Here, rice (Oryza sativa L.) plants were engineered to constitutively overexpress the rice GDP-L-gala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 90 publications
0
19
0
Order By: Relevance
“…As an example of this variability in experimental approaches, contrasting results regarding the effect of overexpressing VTC2 on plant growth and stress tolerance have been reported. For instance, Zhang et al ( 2015 ) described improved seedling biomass in salt-stressed rice plants overexpressing A. thaliana VTC2 , while subsequent studies in rice did not show significant variations in terms of shoot biomass when overexpressing the kiwifruit ortholog (Ali et al, 2019 ) or the OsVTC2 counterpart (Broad et al, 2020 ). Again, one important limitation of the conclusions reached by Zhang et al ( 2015 ) is that biomass results were expressed on a fresh-weight basis instead of on a dry-weight basis, as mandatory when working with water-deficit stresses.…”
Section: Discussionmentioning
confidence: 99%
“…As an example of this variability in experimental approaches, contrasting results regarding the effect of overexpressing VTC2 on plant growth and stress tolerance have been reported. For instance, Zhang et al ( 2015 ) described improved seedling biomass in salt-stressed rice plants overexpressing A. thaliana VTC2 , while subsequent studies in rice did not show significant variations in terms of shoot biomass when overexpressing the kiwifruit ortholog (Ali et al, 2019 ) or the OsVTC2 counterpart (Broad et al, 2020 ). Again, one important limitation of the conclusions reached by Zhang et al ( 2015 ) is that biomass results were expressed on a fresh-weight basis instead of on a dry-weight basis, as mandatory when working with water-deficit stresses.…”
Section: Discussionmentioning
confidence: 99%
“…Salinity, drought, and temperature stresses can cause ROS accumulation, resulting in severe oxidative damage (Cruz de Carvalho, 2008;Bhattacharjee, 2013;Choudhury et al, 2017). ROS scavenging is critical for plants to cope with these stresses (Sato et al, 2011;Lisko et al, 2013;Shigeoka and Maruta, 2014;Akram et al, 2017;Laxa et al, 2019;Broad et al, 2020a). Increasing ASC content by promoting ASC synthesis can enhance ROS scavenging ability and significantly improve plant stress tolerance (Hemavathi et al, 2000;Wang et al, 2011bWang et al, , 2018Lisko et al, 2013;Ma et al, 2014;Ali et al, 2019;Broad et al, 2020a;Gaafar et al, 2020).…”
Section: As An Antioxidant Asc Effectively Scavenges Ros and Enhances Abiotic Stress Tolerancementioning
confidence: 99%
“…ROS scavenging is critical for plants to cope with these stresses (Sato et al, 2011;Lisko et al, 2013;Shigeoka and Maruta, 2014;Akram et al, 2017;Laxa et al, 2019;Broad et al, 2020a). Increasing ASC content by promoting ASC synthesis can enhance ROS scavenging ability and significantly improve plant stress tolerance (Hemavathi et al, 2000;Wang et al, 2011bWang et al, , 2018Lisko et al, 2013;Ma et al, 2014;Ali et al, 2019;Broad et al, 2020a;Gaafar et al, 2020). In contrast, disruption of ASC de novo synthesis significantly reduces plant stress tolerance (Conklin et al, 1996;Noctor and Foyer, 1998;Huang et al, 2005;Qin et al, 2016;Wang et al, 2018).…”
Section: As An Antioxidant Asc Effectively Scavenges Ros and Enhances Abiotic Stress Tolerancementioning
confidence: 99%
See 1 more Smart Citation
“…Although currently there are still only a handful of studies looking into this particular aspect, the information gathered from transcriptomics analyses can provide useful insights into the molecular players governing both traits, along with the identification of potential biomarkers to test seed quality. Several studies reported poor germination in different lines of biofortified rice [ 31 , 32 , 33 ], while in other cases, agricultural biofortification (e.g., soil or foliar application of zinc or selenium) proved to be beneficial for germination [ 34 , 35 ]. The current advances in omics can now provide tools and techniques for the efficient exploration of genetic resources along with a better understanding of the molecular mechanisms involved in trait development.…”
Section: Introductionmentioning
confidence: 99%